Case Report: Chemoimmunotherapy in microsatellite-instability-high advanced goblet cell carcinoma of the colon - Mutlu, Arda Ulaş; Aytaç, Erman; Gülmez, Mehmet; Erdamar, Sibel; Özer, Leyla (Frontiers in Immunology, 2023)
Background Mismatch repair (MMR) deficiency is a fundamental factor affecting the management treatment outcomes of colorectal cancer (CRC). MMR status can be diagnosed by both immunohistochemistry (IHC) polymerase chain reaction (PCR). Since tumors with MMR deficiency are prone to respond to immunotherapy immune checkpoint inhibitors are used to treat such tumors. Case presentation A 69-year-old male patient presented to an outside clinic with weight loss and abdominal pain. Radiological investigations detected a mesenteric mass of 10 cm, peritoneal implants, and mediastinal lymphadenopathy. The eventual biopsy result from the mesenteric mass was mucinous adenocarcinoma with a goblet cell pattern. Since the IHC result was unclear for deficiency in mismatch repair (dMMR) metastatic CRC (mCRC), the diagnosis was confirmed with PCR. The patient received 8 cycles of FOLFIRINOX + bevacizumab followed by FOLFOX combined with pembrolizumab. No adverse effect was reported related to immunotherapy which resulted in radiologic and metabolic regression. The patient underwent cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC). The final pathology results revealed a pathological complete response and R0 resection. In the 6th month follow-up, no recurrence or metastasis was reported. Conclusion Chemotherapy and immunotherapy combination is a promising treatment modality which can also be used for mCRC. This is the index case who received chemotherapy in combination with immunotherapy for mucinous adenocarcinoma of the colon with a goblet cell pattern and had pCR.